Little Ice Age drought in equatorial Africa: Intertropical Convergence Zone migrations and El Nino-Southern Oscillation variability RID C-1423-2010 - Russell, J. M.; Johnson, T. C. (Geology, 2007)
High-resolution analyses of the Mg concentration in authigenic calcite in five cores from Lake Edward provide a water balance history of central equatorial Africa spanning the past 1400 yr. A high ratio of Mg to Ca (%Mg) indicates strong droughts in central Africa during the Little Ice Age (A.D. 1400-1750), in contrast to records from Lake Naivasha, Kenya, which suggest a wet Little Ice Age. This spatial pattern in Africa likely arose due to coupled changes in the high latitudes, the position of the Intertropical Convergence Zone, and the Ell Ni (n) over tildeo-Southern Oscillation (ENSO) system. Our results further suggest that the patterns and variability of twentieth-century rainfall in central Africa have been unusually conducive to human welfare in the context of the past 1400 yr.
id: 2049; PT: J; UT: WOS:000243483800006